1992
DOI: 10.1103/physrevlett.68.1722
|View full text |Cite
|
Sign up to set email alerts
|

Injection and sustainment of plasma in a preexisting toroidal field using a coaxial helicity source

Abstract: The spheromak device SPHEX has been modified by adding a current-carrying rod along the geometric axis, providing a preexisting toroidal field. We show that plasma can be successfully injected into such a field from a helicity source; the field assists plasma ejection from the gun and improves the coupling between gun and plasma, so that T^., Ti, and the toroidal current all increase with rod current. The mechanism of plasma sustainment appears to be the same as that of the spheromak. These results represent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 8 publications
5
32
0
Order By: Relevance
“…Experiments were performed on a spheromak with a current-carrying central rod (a rodomak) [43]. It was found that a pre-existing toroidal field improves energy coupling from the gun to the plasma.…”
Section: Appendix 2 Recent Results From the Sphex Experimentsmentioning
confidence: 99%
“…Experiments were performed on a spheromak with a current-carrying central rod (a rodomak) [43]. It was found that a pre-existing toroidal field improves energy coupling from the gun to the plasma.…”
Section: Appendix 2 Recent Results From the Sphex Experimentsmentioning
confidence: 99%
“…The MHD dynamo is widely thought to underlie planetary, stellar, and galactic disk magnetism (e.g., Zeldovich et al 1983;Kulsrud et al 1997;Beck et al 1996;Vallée 2004), while magnetic relaxation is the preferred route for the spontaneous formation of a device-scale magnetic field in laboratory experiments such as the spheromak (e.g., Jarboe 1994;McLean et al 2002;Hsu & Bellan 2005), reversed-field pinch (e.g., Bodin & Newton 1980;La Haye et al 1986;Dexter et al 1991), spherical tokamak under external coaxial magnetic helicity injection (e.g., Jarboe 1989;Browning et al 1992;Nelson et al 1994;Nagata et al 2003;Tang & Boozer 2007), and the concept of a spherical tokamak with a plasma center column (ST-PCC: Tang & Boozer 2006). These two paradigms differ in that: (1) MHD dynamo operates on the premise of an energetic plasma flow and converts the flow energy into magnetic energy, while (2) magnetic relaxation is a process by which magnetic helicity and magnetic energy injected on small scales from the source are transported to and accumulated on system-scale magnetic fields via small-amplitude plasma fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…The spherical tokamak concept was tested in the late eighties by the insertion of current-carrying central rods into small existing devices [2][3] [4]. These experiments were limited to cold plasmas (electron temperatures of a few tenths of eV) but gave evidence to the advantage of combining the favorable characteristics of both the compact torus and the conventional tokamak.…”
Section: Spherical Tokamak Experiments Worldwidementioning
confidence: 99%